Hitler's secret conversations, 1941-1944 - With an introductory essay on The Mind of Adolf Hitler, by H. R. Trevor-Roper. (Signet, 1961)
London ed. has title: Table talk, 1941-1944. "The original Bormann-Vermerke ... translated in full."